Bimetallic Au-Ag nanorod dimers as plasmonic biosensors - Rahman, Md Ahnaf; Hossain, Aishik; Hossain, Mohammed Shadman (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.